International crimes and ICC cooperation in England and Wales - Cryer, Robert (Journal of international criminal justice, 2010)
The United Kingdom, as a party to the ICC Statute, has brought in a series of similar pieces of legislation in order to fulfil its obligations under the Statute, and to ensure that crimes subject to the jurisdiction of the ICC are also crimes in domestic law. This article concentrates on the International Criminal Court Act 2001, which applies in England and Wales, to appraise whether it adequately provides for assistance to the ICC, and whether the crimes subject to the ICC's jurisdiction are adequately incorporated into domestic law. The article also mentions the possible role of the common law of England and Wales in relation to international crimes. It concludes that, for the most part, the Act reflects a sensible approach to issues involved in assisting the ICC and provides a workable basis for the prosecution of international crimes in that jurisdiction